Assessing the Effect of a Mobile Application on Cancer Risk Health Literacy: A Cross-Sectional Study Design - Westerlinck, Philippe; Maes, Nathalie; Coucke, Philippe (Applied Clinical Informatics, 2025)
Background The “cancer risk calculator” mobile application aims to inform patients about their personal risks of cancer and the risk factors influencing said risks. The present analysis examines the responses to a questionnaire submitted by oncology patients treated with radiotherapy or their family members.Objective The primary objective was to determine the effect of the app on the user's awareness and potential habit changes related to cancer risk. Further, the study aimed to discern any relationships between respondent characteristics and their questionnaire responses.Methods A total of 162 patients were included in the analysis. Each patient's dataset comprised gender, date of birth, entry date, respondent type, type of cancer, and responses to 12 application-related questions. Statistical methods such as multiple regression models were employed to identify any effects of the respondent's characteristics on their responses. Statistical significance was set at p < 0.05.Results Responding to the survey questions, 67.1% of respondents found the application useful, and 63.4% reported learning something new. More than half (52.5%) indicated a willingness to change their habits based on the information provided. Respondents also indicated that they were surprised by the number of risk factors shaping their risks and the large influence of some of these risk factors. Variables such as breast cancer diagnosis (p = 0.044) and age (p = 0.049) influenced specific question responses.Conclusion The “cancer risk calculator” app appears to have a significant utility in educating its users about cancer risk and potentially influencing habit change.
Keywords: cancer risk calculator; patient education; habit change; mobile application; cancer awareness; health literacy